1994
DOI: 10.1016/0370-2693(94)90201-1
|View full text |Cite
|
Sign up to set email alerts
|

Parafermions, W strings and their BRST charges

Abstract: We show how to relate the parafermions that occur in the W 3 string to the standard construction of parafermions. This result is then used to show that one of the screening charges that occurs in parafermionic theories is precisely the non-trivial part of the W 3 string BRST charge. A way of generalizing this pattern for a W N string is explained. This enables us to construct the full BRST charge for a W 2,N string and to prove the relation of such a string to the algebra W N−1 for arbitrary N , We also show h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…By taking repeated operator products of e iφ 1 with itself it can be shown that, in terms of φ 1 and φ 2 , Q 1 takes the simple form [7] …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By taking repeated operator products of e iφ 1 with itself it can be shown that, in terms of φ 1 and φ 2 , Q 1 takes the simple form [7] …”
mentioning
confidence: 99%
“…This can be simplified further by defining a new fieldφ 1 in terms of φ 1 by means of the relations [7] e iφ 1 = i∂φ 1 e −iφ 1…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in constructing BRST charges for higher spin strings (e.g. W 2,N or W N strings) has been made in [29].…”
Section: Discussionmentioning
confidence: 99%
“…Explicit solutions have been found for all s ≤ 8 [2,3], and general existence arguments for one class of solutions for all values of s were given in Refs. [9,2]. Now we turn to the construction of the non-critical BRST operators for W M 2,s ⊗ W L 2,s ′ .…”
mentioning
confidence: 99%